LC-MS/MS를 이용한 축산물 중 유기주석계 농약 Azocyclotin, Cyhexatin 및 Fenbutatin oxide의 동시시험법 개발 - 김남영; 박은지; 박소라; 이정미; 정용현; 윤혜정; Nam Young Kim; Eun-Ji Park; So-Ra Park; Jung Mi Lee; Yong Hyun Jung; Hae Jung Yoon (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2023)
축산물 중 잔류허용기준이 설정되어 관리하고 있는 농약 azocyclotin, cyhexatin, fenbutatin oxide는 대표적인 유 기주석계 살비제이다. 기존 시험법은 가스크로마토그래피 를 사용하여 정량한계가 높고 분석 시 재현성이 떨어져 이에 대한 개선이 필요한 실정으로 본 연구에서는 비교적 간편하며 시간이 적게 소요되는 QuEChERS법을 활용하여 azocyclotin, cyhexatin, fenbutatin oxide의 시험법을 마련하 고자 하였다. 1% 아세트산을 함유한 아세트산에틸:아세토 니트릴(1:1) 혼합액을 이용하여 진탕 추출 후 d-SPE로 정 제하고 이를 농축 후 LC-MS/MS를 이용한 시험법을 개발 하였다. Azocyclotin, cyhexatin 및 fenbutatin oxide의 결정 계수(R2)는 0.99 이상으로 높은 직선성을 확인하였으며 정 량한계는 0.01 mg/kg으로 높은 감도를 나타내었다. 대표 축산물 5종(소, 돼지, 닭, 계란, 우유)에서 LOQ(0.01 mg/ kg), MRL(0.05 mg/kg), MRL 10배(0.5 mg/kg)의 농도에서 회수율 실험을 한 결과 평균 회수율이 76.4-115.3% 및 84.4-110.8%이었으며, 상대표준편차는 25.3% 이하로 나타 났다. 본 연구는 Codex 가이드라인(CAC/GL 40-1993, 2003) 및 ‘식품의약품안전처 식품의약품안전평가원의 식 품등 시험법 마련 표준절차에 관한 가이드라인(2016)’에 적합한 수준임을 확인하였다. 따라서 본 연구에서 확립한 시험법은 축산물 중 잔류할 수 있는 azocyclotin, cyhexatin, fenbutatin oxide의 안전관리를 위한 공정시험법으로 활용 가능할 것으로 판단된다. Organotin pesticide is used as an acaricide in agriculture and may contaminate livestock products. This study aims to develop a rapid and straightforward analytical method for detecting organotin pesticides, specifically azocyclotin, cyhexatin, and fenbutatin oxide, in various livestock products, including beef, pork, chicken, egg, and milk, using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The extraction process involved the use of 1% acetic acid in a mixture of acetonitrile and ethyl acetate (1:1). This was followed by the addition of anhydrous magnesium sulfate (MgSO4) and anhydrous sodium chloride. The extracts were subsequently purified using octadecyl (C18) and primary secondary amine (PSA), after which the supernatant was evaporated. Organotin pesticide recovery ranged from 75.7 to 115.3%, with a coefficient of variation (CV) below 25.3%. The results meet the criteria range of the Codex guidelines (CODEX CAC/GL 40). The analytical method in this study will be invaluable for the analysis of organotin pesticides in livestock products.